Ionic Liquid‐Mediated Transdermal Delivery of Thrombosis‐Detecting Nanosensors - Bekdemir, Ahmet; Tanner, Eden E. L.; Kirkpatrick, Jesse; Amini, Ava; Mitragotri, Samir; Bhatia, Sangeeta N. (Advanced Healthcare Materials, 2022)
Blood clotting disorders such as pulmonary embolism are associated with high morbidity and mortality. A large portion of thrombotic events occur postoperative and after hospital discharge. Therefore, easily applicable, noninvasive, and long-term monitoring of thrombosis occurrence is critical for urgent clinical intervention. Here, the use is proposed of ionic liquids as a skin transport facilitator to deliver thrombin-sensitive nanosensors that enable prolonged monitoring of pulmonary embolism. Co-formulation of nanosensors with choline and geranic acid (CAGE) ionic liquids demonstrates significant transdermal diffusion into the dermis of the skin and provides sustained release into the blood throughout 72 h. Upon reaching the systemic circulation, the nanosensors release reporter molecules into the urine by responding to activation of the clotting cascade and retain a diagnostic power for 24 h in an acute pulmonary embolism mouse model. These results demonstrate a proof-of-concept disease monitoring system that can be topically applied by patients and potentially reduce mortality and high cost of hospitalization.